The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.29244/mikm.12.1.25-34
|View full text |Cite
|
Sign up to set email alerts
|

Penetapan Skala Industri Batik Rumahan Menurut Kriteria Lokal: Studi di Desa Jarum, Kabupaten Klaten

Abstract: Bayat Sub-district of Klaten Regency has been supplying batik to Yogyakarta and Surakarta since the 1960’s. The role of Bayat as a batik provider is inseparable from Jarum village, which was officially established as a tourism village by the Government of Klaten Regency in 2014. Considering that batik is produced under Putting Out System (POS) which employs home workers, the industrial scale criteria applied to formal industry is less appropriate if it will be applied to batik home-industry as a micro-small sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
3
0
2
Order By: Relevance
“…Workers for coloration or the dyers were paid for IDR 25,000 to IDR 75,000 per day or IDR 50,000 per day on average, while buruh nyanthing were paid of IDR 25,000 to IDR 50,000 per day or IDR 37,500 per day on average (Table 1.). Those who work in coloration were considered to work harder than those who do nyanthing, and they were paid differently due to this reason (Handayani et al, 2017). We observed that in addition to coloration, the workers were responsible for boiling and washing the clothes and put them under the sunlight for drying (Figure 4).…”
Section: The Batik Workers: Buruh Harian and Buruh Borong Lepasmentioning
confidence: 96%
See 2 more Smart Citations
“…Workers for coloration or the dyers were paid for IDR 25,000 to IDR 75,000 per day or IDR 50,000 per day on average, while buruh nyanthing were paid of IDR 25,000 to IDR 50,000 per day or IDR 37,500 per day on average (Table 1.). Those who work in coloration were considered to work harder than those who do nyanthing, and they were paid differently due to this reason (Handayani et al, 2017). We observed that in addition to coloration, the workers were responsible for boiling and washing the clothes and put them under the sunlight for drying (Figure 4).…”
Section: The Batik Workers: Buruh Harian and Buruh Borong Lepasmentioning
confidence: 96%
“…Based on our previous research, there are 31 batik industries in the village, 19 of which produce batik cloth, 10 industries produce batik on woodcraft, an industry produces batik on T-shirt, and another industry produces batik paintings (Handayani et al, 2017). However, we focused on batik cloth production as female homeworkers get involved in hand drawing batik, and that batik cloth industries comprise about 61% of total batik industries in Jarum.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Hal tersebut mendorong peningkatan ekspor batik yang dapat menambah pendapatan negara dan meningkatkan lapangan kerja. 3 Nilai Ekspor pada tahun 2011 sebesar Rp 43,96 triliun meningkat menjadi Rp 50,44 triliun di tahun 2015, selain itu terjadi peningkatan unit usaha batik sebesar 14,7% selama kurun waktu lima tahun tersebut. 4 Selain menghasilkan dampak positif berupa peningkatan pendapatan negara, namun industri kerajinan batik juga menghasilkan limbah pewarna kimia yang berpotensi mencemari lingkungan perairan dan juga berbahaya bagi manusia.…”
Section: Pendahuluanunclassified
“…Desa Wisata Jarum mempunyai 19 UMKM Batik yang terbagi menjadi tiga berdasarkan skala usahanya. Terdapat 7 UMKM Batik yang berskala besar, 4 UMKM Batik yang berskala sedang, dan 8 UMKM Batik yang berskala kecil (Handayani, Hunga, & Kristijanto, 2017). Syarat untuk menjadi responden harus berdomisili di Desa Wisata Jarum dan saat penelitian berlangsung sedang bekerja sebagai pengrajin batik tulis.…”
Section: Metode Penelitian a Identifikasi Respondenunclassified